Hubungan Tingkat Kepuasan Pelayanan Makanan dengan Tingkat Kecukupan Zat Gizi Makro pada Pasien Non Diit Rawat Inap Kelas III di RS Bhayangkara Bandar Lampung - Ridha Anggraini Rio; Dera Elva Junita (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
High-quality food service can enhance patient satisfaction and positively impact nutritional adequacy, thereby accelerating recovery and preventing complications. This study aims to analyze the relationship between the level of satisfaction with food service and the adequacy of macronutrient intake in non-diet meals among Class III inpatients at Bhayangkara Hospital, Bandar Lampung. This research employed a quantitative analytical method with a cross-sectional approach involving 133 patients as the population and 102 patients selected through random sampling during October–December 2024. Research instruments included a food service satisfaction questionnaire, a 2 × 24-hour food recall form, a food weighing form to measure leftover food, and the NutriSurvey application to calculate nutrient intake. Data were analyzed using univariate and bivariate analysis with the gamma test and presented in percentages. The results showed a significant relationship between satisfaction with food service and the adequacy of macronutrients, including energy (p-value = 0.000), protein (p-value = 0.012), fat (p-value = 0.000), and carbohydrates (p-value = 0.000), indicating that food service satisfaction influences patients’ macronutrient intake. Therefore, hospitals are recommended to continuously improve the quality of food services to support adequate macronutrient intake.